Sperm meiotic segregation, aneuploidy and high risk of delivering an affected offspring in carriers of non-Robertsonian translocation t(13;15) - Kasikova, Katerina; Vozdova, Miluse; Prinosilova, Petra; Gaillyova, Renata; Hanakova, Marta; Rubes, Jiri (Journal of assisted reproduction and genetics, 2012)
PURPOSE: To determine the percentage of unbalanced spermatozoa and an interchromosomal effect in two carriers of balanced translocations t(13;15)(q32;q26) and t(13;15)(q32;p11.2). METHODS: Sperm nuclei analysis by fluorescent in situ hybridization for detection of percentage of unbalanced spermatozoa and sperm with disomy of chromosomes X, Y, 8, 18, 21 and diploidy. RESULTS: The incidence of unbalanced spermatozoa was 50.5 % and 44.6 % in patient 1 (P1) and patient 2 (P2), respectively. Partial disomy of chromosome 13 was detected in 13.4 % and 21.3 % of sperm in P1 and P2, respectively. The unbalanced karyotype der(15)t(13;15) was found previously in a son of P1 and in two adult relatives, and prenatally in the family of P2. This demonstrates a high risk of delivering an affected offspring. Significantly increased frequencies of chromosomes 8, 18, X and XY disomy and diploidy were observed in P2, which might either indicate an interchromosomal effect or be related to his asthenoteratozoospermia. CONCLUSIONS: Since the proportions of unbalanced spermatozoa and the risk of delivering an affected offspring are high, prenatal or preimplantation genetic diagnosis is recommended for such patients.
Keywords: dospělí; Meiosis; aneuploidie; segregace chromozomů; spermie; Adult; meióza; lidské chromozomy, pár 13; Spermatozoa; prenatální diagnóza; lidé; Translocation, Genetic; Prenatal Diagnosis; Chromosomes, Human, Pair 13; karyotyp; Chromosomes, Human, Pair 15; lidské chromozomy, pár 15; Male; Karyotype; hybridizace in situ fluorescenční; mužské pohlaví; translokace genetická; Aneuploidy; In Situ Hybridization, Fluorescence; Chromosome Segregation; Humans